The Influence of Village Apparatus Competence, Village Organizational Culture and Village Head Leadership on Community Satisfaction Kwala Serapuh Langkat Village - Wahyono, Teguh; Pratama, Siswa; ,, Erwansyah; Sari, Maya (Universitas Negeri Medan, 2024)
This study aims to analyze the influence of three main factors, namely the competence of village officials, village organizational culture, and village head leadership on the level of community satisfaction in Kwala Serapuh Village, Langkat. The first factor studied is the level of competence of village officials. This includes their ability to carry out administrative tasks, knowledge of village regulations, and the ability to communicate with the community. This research will identify the extent to which the competence of village officials affects the community's perception of village services and performance. The village organizational culture includes the norms, values, and practices that govern the interaction between village officials and their relationship with the community. The number of samples in this study was 100 respondents. The research method used is multiple linear regression analysis with the help of the SPSS version 25 program. The results of the study show that the Competence of Village Apparatus has a significant positive effect on Community Satisfaction. Organizational Culture has no positive and insignificant effect on Community Satisfaction. The leadership of the Village Head does not have a significant positive effect on Community Satisfaction. Meanwhile, simultaneously the Competence of the Village Apparatus, the Organizational Culture and the Leadership of the Village Head together have a significant positive effect on Community Satisfaction. The contribution of the magnitude of influence is 52.6%.